PENGENDALIAN INTERN DAN PARTISIPASI MASYARAKAT DALAM MENGURANGI KECENDRUNGAN KECURANGAN PENGELOLAAN DANA DESA DI KECAMATAN BATUKLIANG KABUPATEN LOMBOK TENGAH - Kisnawati, Baiq; Irianto, Irianto; Siswandi, Hendra (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2019)
This study aims to determine the role of internal control and public cparticipation in reducing the tendency of fraud in managing village funds in e Batukliang district of Central Lombok. The research method used a qualitative method approach with descriptive research types. The study was conducted in Batukliang district which consisted of 10 villages. For internal control variables, 10 respondents used were village secretaries taken from each village. While for the variable of public participation used 10 respondents, the respondents used ware one hamlet head for each village taken randomly. The results showed that internal control was seen from the control environment, risk setting, control activities, application of information and monitoring systems, on average 76% of respondents gave very important answers, 8% answered their roles and 16% answered enough to play a role. So it can be concluded that internal control plays an important role in reducing the fraud tendency of managing village funds in Batukliang district of Central Lombok. While community participation both in terms of planning and implementation aspects play a very important role in reducing the fraud tendency in the managing the village funds in the Batukliang district of Central Lombok Regency because 100% of respondents gave  very role answer